Pregnancy outcomes in women with thalassemia major and minor: an observational cross-sectional study - Begum, Umme A. M.; Saha, Eti; Meherunnesa, Syeda; Khatun, Tahmina; Haq, A. F. M. Ashikul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Recent advances in the management of thalassemia have significantly improved life. Expectancy and quality of life in patients with this hemoglobinopathy result in a consequent increase in their reproductive potential and desire to have children. This study aimed to assess the pregnancy outcome in thalassemia patients. Methods: This observational cross-sectional study was conducted at the Department of Obstetrics and Gynaecology of Bangabandhu Sheikh Mujib Medical University and Dhaka Medical College, Dhaka, Bangladesh, from October 2014 to March 2015. A total of 50 admitted patients in the Obstetrics and Gynaecology wards of BSMMU in the set duration of 6 months; the pregnant patients with thalassemia were enrolled in this study purposively. Data were analyzed using Microsoft Office tools. Results: The data analysis of 50 patients yielded the following results. The mean age of 50 mothers was 27.67 (±7.59) years. The maximum 36 (72%) patients were from the 21-30 years’ age group. Among the 50 mothers with thalassemia, 8 (16%) were diagnosed with thalassemia major, and the remaining 42 (84%) were diagnosed with thalassemia minor. Pregnancy was relatively less complicated in the mothers with thalassemia major, as they were under regular ANC and regular supervision of hematologists, so that they could avoid pregnancy-induced thalassemia-related complications. But most thalassemia minor cases were undiagnosed or less emphasized before they became pregnant. So, they faced more complications. A total of 48 (96%) mothers gave birth successfully. Every mother bore a singleton pregnancy. 7 (14%) were born with low birth weight. Among them, 2 (28.57%) were found as intra uterine devices (IUDs). APGAR scores of neonates at 1 min <7 were found in case of 8 cases (16%), and at 5 min were 3 (6%). 12 (24%) babies required ICU admission. Conclusion: Pregnancy is possible, safe, and usually has a favourable outcome in patients with thalassemia, in the presence of a multidisciplinary team.